Analisis Karakteristik Daun Dan Batang Tumbuhan Aucuba Japonica Di Kawasan Kecamatan Cibiru, Kota Bandung (International Forum of Researchers and Lecturers, 2025)
The Garryaceae family is referred to as one of the Cornaceae groups or dicotyledonous plants. Garrya is an evergreen shrub or small tree that bears male flowers. Garraceae is also a shrub that contains alkaloids. Aucuba japonica or what is often referred to as Japanese Laurel is a shrub with unique colored leaves that have spots. Research on the Garryaceae family is still rare, therefore researchers conducted research on the Garryaceae family, especially on the Aucuba japonica species. This research was conducted to analyze the characteristics of the leaves and stems of Aucuba japonica in the Cibiru District area, Bandung City, especially at the Biological Gardens of UIN Sunan Gunung Djati Bandung. This analysis was carried out using exploration methods and literature studies related to Aucuba japonica. The research results showed that there were 37 Aucuba japonica species in the biological garden area of ​​UIN Sunang Gunung Djati Bandung. The characteristic shape of the leaves is oval or elliptical with tapered or blunt tips. The edges of the leaves have a serrated or curved shape with wavy edges. The base of the leaves is round or tapered. The arrangement of the leaves has pinnate veins that branch and spread throughout the leaf blade. the flesh of the leaves is thick and leathery. The surface of the leaves is shiny and smooth, while the stem has woody characteristics (lignosus), the surface of the stem is rough and has a hard texture. Aucuba japonica stems have sympodial branching.